Post-Katrina Recovery of the Housing Market Along the Mississippi Gulf Coast - McCarthy, Kevin F. (RAND Corporation, 2008)
In summer 2006, the Commission on Recovery, Rebuilding, and Renewal asked the RAND Gulf States Policy Institute to describe the state of the pre-Hurricane Katrina housing markets in Mississippi's three coastal counties, to estimate the damage the storm did to their housing markets, to describe the status of the recovery effort, and to identify problems that might inhibit it. This report publishes the findings.